Inpatient rehabilitation did not positively affect 6‐month patient‐reported outcomes after hip or knee arthroplasty. Issue 10 (2nd September 2018) - Hutchinson, Adam G.; Gooden, Benjamin; Lyons, Matthew C.; Roe, Justin P.; O'Sullivan, Michael D.; Salmon, Lucy J.; Martina, Kaka; Pinczewski, Leo A.
Abstract : Background: The aim of this study was to compare patient‐reported outcomes 6 months after hip or knee arthroplasty in subjects who were discharged to home compared to those who attended inpatient rehabilitation. Methods: Seven hundred and forty‐eight consecutive total hip or knee replacement patients were identified from a prospective database. Preoperative and 6‐month post‐operative patient‐reported outcome measures were recorded. Forty‐four patients discharged directly to home were cohort matched by age, gender, procedure and surgeon to 44 patients from the cohort who received inpatient care. Patient outcomes were compared using SPSS version 24 software. Results: Both cohorts saw significant improvements from baseline at 6 months. Median length of rehabilitation for the inpatient group was 7 days (4–16 days). There was no significant difference between the groups based on patient‐reported outcomes. There was a clinically significant difference ( P = 0.047) in the body mass index of the Home Group (mean = 27) to Rehab Group (mean = 29). Conclusion: Our study has shown that inpatient rehabilitation after hip or knee arthroplasty did not positively affect 6‐month patient‐reported satisfaction, expectation, pain, quality of life, activities of daily living scores, when compared with subjects who were discharged direct to home. A significant average saving of 5600 per patient with the use of home discharge is a promising avenue for health cost reduction, and health resource distribution.